DEVELOPMENT OF METOCLOPRAMIDE HYDROCHLORIDE IN SITU GEL: NASAL DELIVERY AND PHARMACOKINETICS IN NEW ZEALAND RABBITS - UPENDRA C GALGATTE; PRAVIN D CHAUDHARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Systemic bioavailability of metoclopramide hydrochloride (MCH) is 32–80% by oral route. The study was targeted to develop in situ gel of MCH for nasal delivery and to study its pharmacokinetics in healthy rabbits. Pre-systemic metabolism can be overcome. Methods: Poloxamer 407 (P407) aqueous solutions were prepared by cold method. In 32 factorial design, independent variables were Carbopol 934P and polyethylene glycol 6000 (PEG 6000), and dependent responses were gelation temperature, mucoadhesive strength, and drug release. A Pharmacokinetic study was carried out in New Zealand rabbits. The optimized in situ gel (1 mg/ml) was compared with marketed Reglan® (2 mg/2 ml) injection. Area under the curve (AUC), Cmax, and Tmax were estimated. Results: F2 was an optimized formulation. The study showed that P407 solutions formed a gel at nasal temperature 34°C having mucoadhesive strength 806.12±3.45 dyne/cm2. MCH release was found to be 93.74±1.31% within 6 h. Histopathological examination of formulation F2 exhibited safety to the nasal mucosa. The pH of formulations was 5.1±0.1 to 5.6±0.1 in the range of pH of nasal cavity. Plasma samples were analyzed by liquid chromatography/mass spectroscopy (LC/MS). The area under curve AUC0-4 for in situ gel by nasal route was 2716±4.617 ng/h/ml and for marketed solution by intravenous route was 2874±1.0816 ng/h/ml. These were comparable. Nasal bioavailability was found 94.50% from in situ gel. Duration of action was longer, and steady-state concentration was found for in situ gel. Conclusion: In situ gel was capable to release MCH in systemic circulation. In vivo study in rabbits has proved the improved bioavailability of MCH administered nasally. The optimized gel preparation was found to be promising for improved bioavailability.